Incidence and predictors of adverse birth outcomes among women who gave birth at Assosa general hospital, Northwest Ethiopia: a retrospective cohort study - Habtamu Tadesse Gudeta; Shalama Lekasa Nagari; Dessalegn Emana Jabana; Mustefa Aflegn Legese; Demekisa wondimu Biyena; Fantahun Cheklie Kassie (BMC Pregnancy and Childbirth)
Abstract Background Adverse birth outcomes are a significant public health problem worldwide, particularly in low- and middle-income countries. Adverse birth outcomes have significant immediate and long-term health consequences for infants and their families. Understanding the determinants of adverse birth outcomes is crucial to effective interventions. For this purpose, this study aimed to assess the incidence and predictors of adverse birth outcomes among women who gave birth at Assosa General Hospital. Methods An institution-based retrospective cohort study design was used to select 715 mothers who gave birth at the hospital. The study participants were selected by using simple random sampling. Bivariate and multivariable logistic regression analyses were executed to identify predictor variables of adverse birth outcomes. Finally, a multivariable logistic regression model at P-value < 0.05 and adjusted relative risk (ARR) with 95% CI were used to declare predictor variables that were statistically significant with adverse birth outcomes. Result The majority, 465 (65.0%), of mothers were in the 20–34 year age group. The mean age of mothers was 26.9 (± 5.5 SD) years. This study revealed that the incidence of adverse perinatal outcomes was 29.7% (95% CI: 26.3–33.1). The common adverse birth outcomes identified in this study were low birth outcomes (159, 22.2%), preterm birth outcomes (14.8%), birth defects (5.7%), and stillbirth outcomes (3.9%). This study revealed that variables such as antenatal care, hemoglobin, mid-upper arm circumference, malaria status, and hypertension were statistically significant predictors of adverse birth outcomes. Statistically significant independent predictors of adverse birth outcomes were included fewer than 4 prenatal care visits (aRR = 3.53, 95% CI: 1.58, 5.37), malaria cases (aRR = 10.74, 95% CI: 6.56, 17.57), pregnancies with hypertensive disorders (aRR = 3.41, 95% CI: 2.17, 6.47), hemoglobin < 11 g/dl (aRR = 3.68, 95% CI: 2.42, 5.74), and a MUAC < 23 (aRR = 5.90, 95% CI: 3.98, 10.80). Conclusion There was a high incidence of adverse birth outcomes in the study area. This study revealed that inadequate antenatal care follow-up, malaria, hypertension, hemoglobin < 11 g/dl, and a mid-upper arm circumference < 23 cm were predictors of adverse birth outcomes. Governments and health authorities should prioritize policies and programs that are aimed at reducing adverse birth outcomes. Improving maternal health services, nutrition education, early diagnosis, and treatment can help to manage most of these predictors.